Private in public space: The needs of Muslim women in Mosque spaces Case study: Al-Barkah Mosque, Bekasi, Indonesia (ARTEKS : Jurnal Teknik Arsitektur, 2025)
Mosques, as public spaces, function as places of prayer and centers of social, educational, and cultural activity. According to Sharia, Muslim women are not required to worship in mosques, but in some cases, many Muslim women still carry out activities in mosques. Islamic Sharia rules regarding Muslim women in public places, including mosques, should also be applied. The need for privacy for Muslim women in public spaces (mosques) is the subject of this research. This is related to Islamic law, mosque spatial planning, and the use of boundaries in space. The research problem is how the boundaries of mosque spaces accommodate the needs of Muslim women according to Islamic law. The case study is the Al-Barkah Mosque, a grand mosque in Bekasi City. The research method employed is a qualitative descriptive approach with theological analysis, based on Islamic Sharia. Observations were made on the mosque space, including zoning, circulation, and height and material limitations. Interviews were conducted with several Muslim women as users and managers of the mosque. The results of this study are in the form of evaluations and recommendations for mosque space according to the privacy needs of Muslim women at the mosque.